The Criminal Justice System And Technology In The Digital Age - Sandi Yudha Prayoga (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This research utilizes a literature review methodology to examine the legal ramifications of technological advancements on law enforcement practices in the digital era. The burgeoning digital landscape has witnessed a surge in technological developments, such as big data analysis, artificial intelligence, and digital forensics, which have fundamentally reshaped law enforcement operations. This study delves into the positive and negative legal implications of these technologies within the justice system. The findings of this research, gleaned from the reviewed literature, suggest that the application of technology in law enforcement can enhance the efficiency of investigations, facilitate evidence analysis, and improve detainee monitoring. However, there are concomitant legal concerns surrounding privacy and data security that necessitate careful consideration. Furthermore, unequal access to technology and data poses a potential threat to the very concept of equal justice under the law. This research is intended to equip stakeholders in law enforcement and public policy with a comprehensive understanding of the legal ramifications associated with technological innovation. By elucidating these issues, this study also lays the groundwork for future researchers to delve deeper into these complexities through more rigorous empirical research endeavors.